Regulation of the renal sympathetic nerves in heart failure - Ramchandra, Rohit; Barrett, Carolyn J. (Frontiers in Physiology, 2015)
Heart failure (HF) is a serious debilitating condition with poor survival rates and an increasing level of prevalence. Heart failure is associated with an increase in renal norepinephrine spillover, which is an independent predictor of mortality in HF patients. The excessive sympatho-excitation that is a hallmark of heart failure has long-term effects that contribute to disease progression. An increase in directly recorded renal sympathetic nerve activity has also been recorded in animal models of heart failure. This review will focus on the mechanisms controlling sympathetic nerve activity to the kidney during normal conditions and alterations in these mechanisms during heart failure. In particular the roles of afferent reflexes and central mechanisms will be discussed.